PENERAPAN KONSEP â€œTRANSISIONAL KONTEMPORERâ€ PADA PERANCANGAN INTERIOR PERPUSTAKAAN DAERAH PROVINSI BANTEN - Michelle Florencia; Maitri Widya Mutiara; Sri Fariyanti Pane (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
Today there is a lot of competition for education to stay abreast of the very rapid developments of globalization. Education is the primary need of the community where formal education can be obtained, one of which is through the library. Nowadays, public awareness of the importance of reading books is very minimal, so designers need to make changes to the concept of the library to attract people's interest in starting a lifestyle of reading books. Complete facilities, especially in the field of technology, in a library can be one of the attractions for visitors and is equipped with relaxing facilities and a cafÃ© for a short break. In general, libraries are indoor and closed which gives a serious and tense impression so designers provide several digital library innovations with the concept of a learning commons library according to today's lifestyle. Uplifting the 'Transitional Contemporary' style of Banten culture with contemporary culture and 'Natural' style which can produce harmonious designs and do not collide with each other, are able to combine aesthetic elements that complement each other and produce a new room design that feels different. With that, a theme was created